Wild Game: Fresh Meat Processing - Michael Fioretto; Chad Carr; Jason M. Scheffler; Jennifer G. Bearden; Halie Corbitt (EDIS)
This document discusses processing food safety for wild game meat. Topics include aging, carcass cutting, meat grinding, shelf life, freezing, and thawing. Written by Michael Fioretto, Chad Carr, Jason M. Scheffler, Jennifer G. Bearden, and Halie Corbitt, and published by the UF/IFAS Department of Family, Youth and Community Sciences, January 2022.